Ionic liquid facilitated melting of the metal-organic framework ZIF-8 - Vahid Nozari; Courtney Calahoo; Joshua M. Tuffnell; David A. Keen; Thomas D. Bennett; Lothar Wondraczek (Nature Communications, 2021)
The variety of hybrid glasses from metal-organic frameworks (MOFs) has remained strongly limited to only a handful of compounds. Here, the authors introduce a route to melt highly porous and non-meltable MOFs using ionic liquids in order to extend the range of MOF glasses.